(untitled) (Ukrainian Journal of Ophthalmology, 2024)
This paper reviews the current insights into, and prospects for better understanding of, the pathogenesis of optic nerve edema or swelling in the presence of inflammatory or ischemic optic neuropathy. Forty-six Ukrainian and foreign publications on the subject were reviewed and considered. There are several theories of optic nerve damage due to swelling (edema); these include biomechanical theories (features of structural components, a change in the optic nerve architecture, and stretching of the Bruch membrane) and an ischemic theory (abnormal perfusion and axonal transport stasis). Of importance are also abnormal vascular permeability and exudation of plasma and blood cells, which results in accumulation of fluid, inflammatory mediators and metabolic products between peripapillary retinal layers, impeding the outflow and metabolism in the posterior segment of the eye. Current neuroimaging techniques (optical coherence tomography (OCT) and OCT angiography) facilitate improved understanding of structural changes in the optic nerve head. Therefore, studies on optic disc architecture, fluid circulation in the posterior segment, and interaction of optic nerve head components in optic nerve edema or swelling will facilitate (a) improved understanding of the pathogenesis and (b) the differential diagnosis of acute optic neuropathies, and, consequently, will enable treatment for inflammatory and ischemic optic nerve lesions.